PHYSICAL AND MECHANICAL PROPERTIES CEMENT STONE WITH CHEMICAL ADDITIVE KDj-3 (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article presents the results of studies on the use of complex chemical additives KDj-3 to improve the properties of the building mixture. Development and research of concreting technology, reducing water consumption, increasing strength in the initial period (up to 3 days) and energy-saving concretes.